A CsPbBr3 wafer, its preparation method and applications

CN117529187BActive Publication Date: 2026-10-20SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210906075.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2026-10-20
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

相比于太阳能电池和LED等薄膜器件,X射线探测器的制备往往需要消耗更大量的原料

Benefits of technology

本发明提供的制备方法在机械研磨获得大量CsPbBr3钙钛矿粉体的基础上,引入溶剂化处理,一方面可以促进缺陷密度较高的钙钛矿微晶进行再生长,提高微晶的结晶度、降低缺陷密度、提高空气稳定性;另一方面,部分有机溶剂与CsPbBr3钙钛矿形成络合物,在低温退火的过程中促进重结晶,进一步促进晶片表面晶界融合、提高电荷传输性能、降低暗电流,从而可以用于制备高效X射线探测器。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117529187B_ABST
    Figure CN117529187B_ABST
Patent Text Reader

Abstract

The application discloses a kind of CsPbBr3 wafer and its preparation method and purposes, preparation method includes the following steps: PbBr2 and CsBr are obtained by mechanical grinding CsPbBr3 powder;CsPbBr3 powder is dissolved in organic solvent;Reverse solvent is precipitated to obtain CsPbBr3 powder;Tableting;Annealing treatment.The application is based on the mechanical grinding to obtain a large number of CsPbBr3 perovskite powder, introduce solvation treatment, on the one hand, promote the perovskite microcrystalline with higher defect density to regenerate, on the other hand, part of organic solvent and CsPbBr3 form complex, promote the recrystallization in annealing process, effectively improve the crystallinity of wafer, and modify defect, while reducing device dark current, improve device aging stability and carrier transport performance.It has good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite X-ray detection technology, and in particular to a CsPbBr3 wafer, its preparation method, and its uses. Background Technology

[0002] X-ray detection is widely used in medical diagnosis, industrial non-destructive testing, security monitoring, and nuclear reaction monitoring. To reduce radiation damage from high-dose X-rays, higher sensitivity and lower detection limits are required for X-ray detectors. Amorphous selenium is the most common direct X-ray conversion semiconductor material, but its poor charge transport properties and X-ray absorption capacity limit its sensitivity, making it difficult to achieve accurate imaging at low radiation doses. The practical application of Cd(Zn)Te is severely constrained by its high cost and small crystal size.

[0003] In recent years, metal halide perovskites have emerged as promising materials for high-energy X-ray detection due to their large X-ray attenuation coefficient, high carrier mobility, long carrier lifetime, and low defect density. CsPbBr3 single crystals have been proven to possess excellent detection performance, but their growth is time-consuming and their small size makes large-area detection and imaging difficult. Solution-based perovskite film fabrication is a commonly used method for detector preparation, but the poor solubility of all-inorganic materials in solution limits the fabrication of thick films. To effectively absorb X-ray energy, the thickness of the perovskite film often needs to reach several hundred micrometers. To address these issues, a simple pressing process was proposed in Nature Photon 2017, 11, 436–440, using millimeter-scale MAPbI3 wafers for X-ray detection fabrication. However, research on all-inorganic perovskites in this area is still relatively scarce. Compared to thin-film devices such as solar cells and LEDs, the fabrication of X-ray detectors often requires a much larger amount of raw materials. Dry ball milling is more advantageous for large-scale preparation of perovskite powders compared to solution milling, but the products suffer from uncontrollable morphology, numerous defects, and poor stability. Current patents primarily focus on the structural design of X-ray detection devices, with little research on improving material properties and large-scale fabrication for this application.

[0004] In summary, in order to further promote the application of perovskite materials in the field of X-ray detectors, it is necessary to improve the crystal quality of perovskite powder raw materials on a large scale, so as to prepare high-performance X-ray detectors. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a CsPbBr3 wafer, its preparation method, and its application in X-ray detector fabrication. Based on obtaining a large quantity of perovskite powder through mechanical grinding, this invention introduces a mixed solvent to solvate perovskite microcrystals with high defects and uneven morphology, and then uses this solution to fabricate an X-ray detector.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: On one hand, the present invention provides a method for preparing CsPbBr3 wafers, comprising the following steps: Step 1: PbBr2 and CsBr are mechanically ground to obtain CsPbBr3 powder; Step 2: Dissolve the CsPbBr3 powder obtained in Step 1 in an organic solvent; Step 3: The solution obtained in Step 2 is subjected to antisolvent precipitation to obtain CsPbBr3 powder; Step four: Compress the CsPbBr3 powder obtained in step three into tablets; Step 5: Anneal the wafer obtained in Step 4.

[0007] In a preferred embodiment, in step one, the molar ratio of PbBr2 to CsBr is 0.5 to 2:1.

[0008] In a preferred embodiment, the mechanical grinding is ball milling; Preferably, the ball-to-material ratio of the ball mill is 1~5:1, the rotation speed of the ball mill is 200~1000 rpm, and the milling time is 1~6 h; Preferably, the ball-to-material ratio in the ball mill is 1:3, the ball mill rotation speed is 400 rpm, and the ball milling time is 2 hours.

[0009] In a preferred embodiment, in step two, the organic solvent is dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), or a mixture of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF). In the technical solution of this invention, the amount of organic solvent used is sufficient to cover the CsPbBr3 powder, and the dissolution time is approximately 10-60 minutes. In the mixed solvent of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF), the higher the proportion of DMSO, the better the regrowth effect on CsPbBr3 perovskite microcrystals. When the volume ratio of DMSO to DMF is 1:1, the obtained CsPbBr3 perovskite microcrystals have a distinct cubic shape.

[0010] In a preferred embodiment, in step three, the solvent used for antisolvent precipitation is selected from at least one of isopropanol (IPA), acetone, toluene, chlorobenzene, and diethyl ether; In some specific embodiments, the antisolvent precipitation process further includes centrifugation and drying.

[0011] In a preferred embodiment, in step four, the tablet is a tablet compressed under high temperature and high pressure; Preferably, the high pressure is 5~20 MPa; Preferably, the high temperature is 80~150℃; Preferably, when the pressing pressure is 10 MPa and the temperature is 100°C, the resulting wafer has a better surface morphology. In the technical solution of the present invention, wafers with controllable size and thickness can be obtained by selecting molds of different sizes and changing the quality of powder; taking a mold size of 10 mm*10 mm as an example, 180 mg to 300 mg of the above powder can be weighed and wafers with a thickness of 500 μm to 1 mm can be obtained by pressing.

[0012] In a preferred embodiment, in step five, the annealing temperature is 120~200℃; the annealing time is 30 min~2 h, to ensure that the residual solvent has completely evaporated.

[0013] In another aspect, the present invention provides CsPbBr3 wafers obtained by the above preparation method.

[0014] In another aspect, the present invention provides the above-described preparation method or the application of the above-described CsPbBr3 wafer in the preparation of X-ray detectors.

[0015] In some specific embodiments, the fabrication of the X-ray detector includes the steps of fabricating electrodes or fabricating a transport layer and electrodes on the CsPbBr3 wafer; The X-ray detector is: ① a PIN-type or NIP-type photodiode device comprising an active layer, a transport layer, and electrodes, wherein a CsPbBr3 wafer is used as the active layer material; or ② comprising an active layer and electrodes, wherein a CsPbBr3 wafer is used as the active layer material. The material of the transport layer is a commonly used transport layer material in the field, such as one of the following materials or a multilayer structure composed of C60, BCP, PCBM, poly-TPD, PEDOT:PSS, NiOx, PTAA, TAPC, P3HT, TiOX, MoOX, MoO3, V2O5, WO3, etc., and the thickness can be 1 nm to 100 nm. The electrode is made of conventional electrode materials in the art, such as metal electrodes or carbon electrodes made of Cu, Ag, Au, Al, Cr, etc., with a thickness of 50~200 nm.

[0016] The above technical solution has the following advantages or beneficial effects: The preparation method provided by this invention, based on obtaining a large amount of CsPbBr3 perovskite powder through mechanical grinding, introduces solvation treatment. On the one hand, it can promote the regrowth of perovskite microcrystals with high defect density, improve the crystallinity of microcrystals, reduce defect density, and improve air stability. On the other hand, some organic solvents form complexes with CsPbBr3 perovskite, which promote recrystallization during low-temperature annealing, further promoting grain boundary fusion on the wafer surface, improving charge transport performance, and reducing dark current, thus enabling it to be used to prepare high-efficiency X-ray detectors.

[0017] Compared with the prior art, the present invention has the following advantages: 1. By introducing organic solvents for solvation treatment, the regrowth of CsPbBr3 can be effectively promoted, transforming microcrystals with high defect density and irregular shape into blocky microbricks with high crystal quality. 2. During the solvation process, due to the good solubility and affinity of DMSO for PbBr2, a small amount of DMSO is adsorbed into CsPbBr3 powder, forming a CsPbBr3-DMSO complex; when heated at low temperature (less than or equal to 150℃), the DMSO in CsPbBr3-DMSO volatilizes, promoting grain boundary fusion, reducing defects, improving charge transport performance, and obtaining a high-efficiency X-ray detector; 3. This method is simple to operate, novel and unique, and can obtain powders with controllable morphology and high crystal quality without the need for large amounts of solvents and complex and expensive equipment, thus having the potential for large-scale preparation; 4. This method utilizes the regrowth effect of perovskite powder and the complexation effect of DMSO and CsPbBr3 during solvation treatment to prepare high-performance X-ray detectors, which have good application prospects. Attached Figure Description

[0018] Figure 1 This is a flowchart illustrating the fabrication process of the X-ray detector based on a CsPbBr3 wafer in Example 1.

[0019] Figure 2 The image shows a scanning electron microscope (SEM) image of the solvated CsPbBr3 microcrystals obtained in step three of Example 1.

[0020] Figure 3 The images show the photoluminescence (PL) of the CsPbBr3 powder obtained in step one of Example 1 and the CsPbBr3 microcrystals obtained in step three after solvation treatment.

[0021] Figure 4 The images show the X-ray diffraction (XRD) patterns of the ball-milled CsPbBr3 powder obtained in step one of Example 2 and the solvated CsPbBr3 microcrystals obtained in step three.

[0022] Figure 5 These are scanning electron microscope (SEM) images of the surface and cross-section of the wafer prepared in Example 2.

[0023] Figure 6 This is an IV diagram comparing the photocurrent and dark current of the X-ray detector device prepared in Example 3.

[0024] Figure 7 This is the photoresponse diagram of the X-ray detector device prepared in Example 3 under a 5 V bias voltage.

[0025] Figure 8 This is a response diagram of the X-ray detector device prepared in Example 4 to different doses of X-rays under a bias voltage of 20 V. Detailed Implementation

[0026] The following embodiments are merely some, not all, of the embodiments of the present invention. Therefore, the detailed descriptions of the embodiments provided below are not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0027] In this invention, unless otherwise specified, all equipment and raw materials are commercially available or commonly used in the industry. The methods described in the following embodiments are conventional methods in the art, unless otherwise specified.

[0028] Example 1: like Figure 1 As shown, the fabrication process of the CsPbBr3 wafer-based X-ray detector in this embodiment is as follows: Step 1: Weigh 11.01 g of PbBr2 and 6.35 g of CsBr powder raw materials, place them in a ball mill jar, add 50 g of agate balls, and ball mill at 400 rpm for 2 h to obtain 17.36 g of perovskite CsPbBr3 powder. Step 2: Dissolve the CsPbBr3 powder from Step 1 in 8 mL of DMSO. The suspension changes from yellow to green. Step 3: Add isopropanol to the solution from Step 2 to precipitate the precipitate, centrifuge, and dry at room temperature to obtain dry CsPbBr3 powder. Step 4: Weigh 1.5 g of the powder from Step 3, select a mold with dimensions of 10 cm * 10 cm, and press it with a hydraulic press at 100°C and 10 MPa for 10 minutes to press the wafer. Step 5: Anneal the wafer obtained in Step 4 at 150°C for 1 hour; Step 6: Use Ag and Cu as the two end electrodes (150 nm) to vapor deposit the wafer, without adding a transport layer, to complete the fabrication of the X-ray detector.

[0029] In this embodiment, the ball milling product in step one is an irregularly shaped microcrystal with a particle size of 2-5 μm. After solvation treatment in steps two and three, it grows into cubes of 2-12 μm, denoted as CsPbBr3-DMSO microcrystals. Their SEM images are shown below. Figure 2 As shown, the powder quality is very high. The PL results of CsPbBr3 powder before and after solvation treatment in this embodiment are compared as follows: Figure 3 As shown, the luminescence intensity of the CsPbBr3-DMSO microcrystals obtained after solvation treatment increased significantly, indicating that there was a defect passivation effect.

[0030] The wafer thickness pressed in this embodiment is approximately 500 μm, and the device responds well to X-rays.

[0031] Example 2: The fabrication process of the CsPbBr3 wafer-based X-ray detector in this embodiment is as follows: Step 1: Weigh 3.30 g of PbBr2 and 1.87 g of CsBr powder raw materials, place them in a ball mill jar, add 30 g of agate balls, and ball mill at 400 rpm for 2 h to obtain 5.17 g of CsPbBr3 perovskite powder. Step 2: Dissolve the CsPbBr3 powder from Step 1 in a mixed solvent of 2 mL DMSO and 1 mL DMF. The suspension changes from yellow to yellow-green. Step 3: Add toluene to the solution from Step 2 to precipitate the precipitate, centrifuge, and dry at room temperature to obtain dry CsPbBr3 powder; Step 4: Weigh 1.5 g of the powder from Step 3, select a mold with dimensions of 10 cm * 10 cm, and press it with a hydraulic press at 100°C and 10 MPa for 10 minutes to press the wafer. Step 5: Anneal the wafer obtained in Step 4 at 150°C for 1 hour; Step six: Au is directly used as the electrode (150 nm) to vapor deposit on the wafer without adding a transport layer, thus completing the fabrication of the X-ray detector.

[0032] In this embodiment, the crystallinity of CsPbBr3 was significantly improved after solvation treatments in steps two and three, and its XRD signal was compared to that of CsPbBr3. Figure 4 As shown.

[0033] The ball milling product in step one of this embodiment is an irregularly shaped microcrystal with a particle size of 2~5 μm. After solvation treatment in steps two and three, it can grow into cubes with a particle size of 2~12 μm, and the powder quality is very high.

[0034] The wafer pressed in this embodiment has a thickness of approximately 500 μm and is stable under normal temperature and humidity conditions. Both the surface and interface are very dense, and its morphology is as follows: Figure 5 As shown, obvious grain fusion can be observed.

[0035] Example 3: The fabrication process of the CsPbBr3 wafer-based X-ray detector in this embodiment is as follows: Step 1: Weigh 3.30 g of PbBr2 and 1.87 g of CsBr powder raw materials, place them in a ball mill jar, add 30 g of agate balls, and ball mill at 300 rpm for 4 h to obtain 5.17 g of CsPbBr3 perovskite powder. Step 2: Dissolve the CsPbBr3 powder from Step 1 in a mixed solvent of 1 mL DMSO and 1 mL DMF. The suspension changes from yellow to yellow-green. Step 3: Add toluene to the solution from Step 2 to precipitate the precipitate, centrifuge, and dry at room temperature to obtain dry CsPbBr3 powder; Step 4: Weigh 250 mg of the powder from Step 3, select a mold with a size of 10 mm * 10 mm, and use a hydraulic press to press it at 100°C and 10 MPa for 10 minutes to form a wafer. Step 5: Anneal the wafer obtained in Step 4 at 150°C for 1 hour; Step 6: Prepare an X-ray detector with the following structure: Cu (150 nm) — CsPbBr3 wafer — PCBM (30 nm) — C60 (60 nm) — BCP (10 nm) — Ag (150 nm).

[0036] The detector prepared in this embodiment has a good response to X-rays, and its photo-dark current contrast IV diagram is shown below. Figure 6 As shown, it has a large on / off ratio; the response at a 5 V bias is as follows. Figure 7 As shown, the response speed is fast and the baseline is stable.

[0037] Example 4: The fabrication process of the CsPbBr3 wafer-based X-ray detector in this embodiment is as follows: Step 1: Weigh 3.30 g of PbBr2 and 1.87 g of CsBr powder raw materials, place them in a ball mill jar, add 30 g of agate balls, and ball mill at 400 rpm for 2 h to obtain 5.17 g of CsPbBr3 perovskite powder. Step 2: Dissolve the CsPbBr3 powder from Step 1 in 3 mL of DMSO. The suspension changes from yellow to yellow-green. Step 3: Add isopropanol to the solution from step 2 to precipitate the precipitate, centrifuge, and dry at room temperature to obtain dry CsPbBr3 powder; Step 4: Weigh 250 mg of the powder from Step 3, select a mold with a size of 10 mm * 10 mm, and use a hydraulic press to press it at 100°C and 10 MPa for 10 minutes to form a wafer. Step 5: Anneal the wafer obtained in Step 4 at 120°C for 2 hours; Step 6: Prepare an X-ray detector with the following structure: Cu (150 nm) — CsPbBr3 wafer — PCBM (30 nm) — C60 (60 nm) — BCP (10 nm) — Ag (150 nm).

[0038] The detector prepared in this embodiment has a good response to X-rays, and its light response to different doses of X-rays at a bias voltage of 20 V is as follows: Figure 8 As shown, a high sensitivity of 18080 μC G can be obtained through calculation. yair 1 cm 2 .

[0039] Example 5: The fabrication process of the CsPbBr3 wafer-based X-ray detector in this embodiment is as follows: Step 1: Weigh 3.30 g of PbBr2 and 1.87 g of CsBr powder raw materials, place them in a ball mill jar, add 30 g of agate balls, and ball mill at 200 rpm for 6 h to obtain 5.17 g of CsPbBr3 perovskite powder. Step 2: Dissolve the CsPbBr3 powder from Step 1 in a mixed solvent of 1 mL DMSO and 2 mL DMF. The suspension changes from yellow to yellow-green. Step 3: Add diethyl ether to the solution in step 2 to precipitate the precipitate, centrifuge, and dry at room temperature to obtain dry CsPbBr3 powder; Step 4: Weigh 300 mg of the powder from Step 3, select a mold with a size of 10 mm * 10 mm, and press it with a hydraulic press at 150°C and 8 MPa for 15 minutes to press the wafer. Step 5: Anneal the wafer obtained in Step 4 at 120°C for 2 hours; Step six: Prepare an X-ray detector with the following structure: Cu (150 nm) — MoO3 (30 nm) — CsPbBr3 wafer — C60 (60 nm) — BCP (10 nm) — Ag (150 nm).

[0040] Example 6: The fabrication process of the CsPbBr3 wafer-based X-ray detector in this embodiment is as follows: Step 1: Weigh 6.60 g of PbBr2 and 3.74 g of CsBr powder raw materials, place them in a ball mill jar, add 30 g of agate balls, and ball mill at 400 rpm for 2 h to obtain 10.34 g of CsPbBr3 perovskite powder. Step 2: Dissolve the CsPbBr3 powder from Step 1 in a mixed solvent of 5 mL DMF and 1 mL DMSO. The color of the suspension does not change significantly. Step 3: Add diethyl ether to the solution in step 2 to precipitate the precipitate, centrifuge, and dry at room temperature to obtain dry CsPbBr3 powder; Step 4: Weigh 500 mg of the powder from Step 3, select a mold with a size of 15 mm * 15 mm, and use a hydraulic press to press it at 100°C and 20 MPa for 10 minutes to form a wafer. Step 5: Anneal the wafer obtained in Step 4 at 150°C for 2 hours; Step six: Prepare an X-ray detector with the following structure: Cu (150 nm) — MoO3 (30 nm) — CsPbBr3 wafer — C60 (60 nm) — BCP (10 nm) — Au (150 nm).

[0041] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing CsPbBr3 wafers, characterized in that, Includes the following steps: Step 1: PbBr2 and CsBr are mechanically ground to obtain CsPbBr3 powder; Step 2: Dissolve the CsPbBr3 powder obtained in Step 1 in an organic solvent; Step 3: The solution obtained in Step 2 is subjected to antisolvent precipitation to obtain CsPbBr3 powder; Step four: Compress the CsPbBr3 powder obtained in step three into tablets; Step 5: Anneal the wafer obtained in Step 4; In step two, the organic solvent is dimethyl sulfoxide, N,N-dimethylformamide, or a mixture of dimethyl sulfoxide and N,N-dimethylformamide. In step four, the tablet is compressed under high temperature and high pressure; the high pressure is 5~20 MPa; the high temperature is 80~150℃.

2. The preparation method according to claim 1, characterized in that, In step one, the molar ratio of PbBr2 to CsBr is 0.5 to 2:

1.

3. The preparation method according to claim 1, characterized in that, In step one, the mechanical grinding is ball milling.

4. The preparation method according to claim 3, characterized in that, In step one, the ball-to-material ratio of the ball mill is 1~5:1, the rotation speed of the ball mill is 200~1000 rpm, and the milling time is 1~6 h.

5. The preparation method according to claim 4, characterized in that, In step one, the ball-to-material ratio of the ball mill is 1:3, the rotation speed of the ball mill is 400 rpm, and the milling time is 2 hours.

6. The preparation method according to claim 1, characterized in that, In step three, the solvent used for the antisolvent precipitation is selected from at least one of isopropanol, acetone, toluene, chlorobenzene, and diethyl ether.

7. The preparation method according to claim 1, characterized in that, The high pressure is 10 MPa, and the high temperature is 100°C.

8. The preparation method according to claim 1, characterized in that, In step five, the annealing temperature is 120~200℃; the annealing time is 30 min~2 h.

9. The CsPbBr3 wafer obtained by any of the preparation methods described in claims 1-8.

10. The application of the preparation method according to any one of claims 1-8 or the CsPbBr3 wafer according to claim 9 in the preparation of X-ray detectors.